IMPLEMENTASI SYARAT BERPOLIGAMI MENURUT UU NO 1 TAHUN 1974 (STUDI DI KOTA SEMARANG) - Dian Latifiani (Masalah-Masalah Hukum, 2013)
Starting from thoughfulness of many polygamy sirri because of ignorance about the submission requirement of permit polygamy on trial, than do the research about the submission requirement of polygamy. The research is using empirical juridical approaches to fill the polygamy requirement with verification which convince into consideration of judge to give permission. The petition of polygamy is only granted which fill the ruquirements according to Undang-Undang No. 1 Tahun 1974 tentang perkawinan.